ROA DETERMINANTS AND IMPACTS ON CAR (STUDY IN THE FIVE LARGEST PRIVATE BANKS IN INDONESIA 2009-2018) - Salim, M. Noor; Mundung, Lucya Oktavia (Dinasti Publisher, 2020)
This study aims to analyze the effect of Loan to Deposit Ratio (LDR) and Net Interest Margin (NIM) on Return on Assets (ROA) and the influence of Loan to Deposit Ratio (LDR), Net Interest Margin (NIM) and Return on Assets (ROA) to the Capital Adequacy Ratio (CAR) of the five largest private banks in Indonesia in the 2009 - 2018 period. The sample used in this study consisted of 5 conventional private banks listed on the IDX. This study uses panel data obtained from Bank Indonesia reports and annual financial reports that have been audited and published by sample banks on the IDX By using the Fixed Effect Model with the help of Eviews 10, the F test shows that the LDR and NIM variables together have a significant effect on ROA of 77.69% while the remaining 22.31% is influenced by other factors not included in the research model. LDR, NIM and ROA variables together have a significant effect on CAR of 42.85% while the remaining 57.15% are influenced by other factors not included in this study where previously classical assumption tests such as Stationary, Multicollinearity, Test Heteroscedasticity and Autocorrelation test. Based on the results of the t test it was found that the LDR and NIM partially had no significant effect on ROA. LDR has a significant effect on CAR. Meanwhile, NIM and ROA partially had no significant effect on CAR